Calculation of aortic regurgitation orifice area by Doppler echocardiography: an application of the continuity equation. Issue 8 (August 1992) - Yeung, Alan C; Plappert, Ted; Sutton, Martin G St John
Abstract : The evaluation of aortic regurgitation by current echocardiographic techniques has been qualitative and load-dependent. The area of the regurgitant orifice, which is theoretically independent of haemodynamic conditions, has not been determined non-invasively. In 20 patients with various degrees of aortic regurgitation, this area was determined by use of the continuity equation applied during diastole. The velocity-time integrals were determined at the supravalvar (VTIs ) and regurgitant orifice (VTIj ) levels by pulsed and continuous wave Doppler respectively. The cross sectional area at the supravalvar level (As ) was also measured by cross sectional echocardiography. The regurgitant orifice is given by: (As × VTIs )/VTIj . Other non-invasive measurements of the aortic regurgitation severity were also recorded: ( a ) an overall echo score (1–5+) given blindly by two echocardiographers, ( b ) the maximal proximal jet width by colour Doppler, ( c ) left ventricular end systolic and end diastolic volumes and left ventricular mass. The regurgitant area ranged from 0·25 to 1·7 cm 2 and this area accorded with the overall echo score and the maximal proximal jet width measured by colour Doppler. The aortic regurgitation orifice area can be calculated non-invasively and it may be a quantitative measure of the severity of aortic regurgitation.